2016
DOI: 10.2217/bmm-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Monocyte to HDL-Cholesterol Ratio to Predict High SYNTAX Score in Patients with Stable Coronary Artery Disease

Abstract: This study suggests MHR is independently associated with burden of coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 25 publications
6
71
0
4
Order By: Relevance
“…[4][5][6][7][8] As known, HDL-C plays an important role in antiinflammatory, antioxidant and antithrombotic progress, and can inhibit cytokine-induced expression of endothelial cell adhesion molecules. 9,10 It was reported that the MHR was independently associated with coronary atherosclerosis in patients with stable coronary artery disease; 11 however, there is inconsistency in changes in the lymphocyte count in MetS patients. Some studies reported that the number of lymphocytes was decreased in MetS patients, while other studies found that lymphocytes can take part in the pathogenesis of MetS.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] As known, HDL-C plays an important role in antiinflammatory, antioxidant and antithrombotic progress, and can inhibit cytokine-induced expression of endothelial cell adhesion molecules. 9,10 It was reported that the MHR was independently associated with coronary atherosclerosis in patients with stable coronary artery disease; 11 however, there is inconsistency in changes in the lymphocyte count in MetS patients. Some studies reported that the number of lymphocytes was decreased in MetS patients, while other studies found that lymphocytes can take part in the pathogenesis of MetS.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the predictive performance of these biomarkers on the outcomes was limited. More recently, several efficient biomarkers, including gamma-glutamyl transferase (GGT) [25,26], GGT-to-platelet ratio (GPR) [27], mean platelet volume (MPV) [28,29], red blood cell distribution width (RDW) [30,31], and monocyte-to-HDL-C ratio [32], emerged. ALT, mainly derived from the liver, was considered as a marker of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of the SYNTAX score while making revascularization decisions and in predicting adverse events in patients with coronary artery disease has been appreciated in a previous large-scale study [3]. It is known that endothelial dysfunction, oxidative stress, and many inflammatory biomarkers play a crucial role in the formation and progression of atherosclerosis [4][5][6]. Recently, the platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and lymphocyte-tomonocyte ratio (LMR) have been used as inflammatory biomarkers, and have been shown to be independent risk factors for atherosclerosis and cardiovascular events.…”
Section: To the Editormentioning
confidence: 99%